2022
DOI: 10.3847/2041-8213/ac5f02
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of Magnetic Field Spectra at Kinetic Scales of Solar Wind Turbulence as Revealed by the Parker Solar Probe in the Inner Heliosphere

Abstract: Using the Parker Solar Probe data taken in the inner heliosphere, we investigate the power and spatial anisotropy of magnetic field spectra at kinetic scales (i.e., around sub-ion scales) in solar wind turbulence in the inner heliosphere. We find that strong anisotropy of the magnetic spectra occurs at kinetic scales with the strongest power in the perpendicular direction with respect to the local magnetic field (forming an angle θ B with the mean flow velocity). The spectral index of the mag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 60 publications
1
14
2
Order By: Relevance
“…The observation from the Parker Solar Probe (PSP) mission is giving a vital contribution to our research area whereas till now only observations are being reported in the range of 0.17 AU to 0.25AU. A study of the data obtained by PSP shows that the power spectra are steepening in the range of −3.2 to −5.8,as reported by Huang et al (2022). As this PSP continues to follow its path, it will get closer to the solar corona and continue to provide us with more data.…”
Section: Numerical Simulation and Resultssupporting
confidence: 54%
“…The observation from the Parker Solar Probe (PSP) mission is giving a vital contribution to our research area whereas till now only observations are being reported in the range of 0.17 AU to 0.25AU. A study of the data obtained by PSP shows that the power spectra are steepening in the range of −3.2 to −5.8,as reported by Huang et al (2022). As this PSP continues to follow its path, it will get closer to the solar corona and continue to provide us with more data.…”
Section: Numerical Simulation and Resultssupporting
confidence: 54%
“…Inertial range spectral anisotropy has been investigated by (Huang et al 2022;Wu et al 2022), who used slow solar wind data from E1 of PSP to show that the spectral indices are close to −5/3 and −3/2 in the parallel and perpendicular direction, respectively. (Wu et al 2022) also compared the anisotropic spectral properties of the slow wind stream sampled by PSP during E1 to a fast wind, V sw ≈ 770 km s −1 , Ullyses stream at 1.48 au and concluded that the differences between the near-Sun and near-Earth solar wind likely result from the existence of two sub-ranges in the inertial range, with the one closer to kinetic scales (∼ 30d i − 300d i ) displaying a radial steepening, while the one at larger scales remains unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…However, detailed comparisons are beyond the scope of the current study. Recent studies also indicate correlation anisotropy (Cuesta et al 2022) and anisotropy of the energy spectrum (Huang et al 2022;Zhang et al 2022) in the PSP datasets, which may suggest anisotropy of nonlinear energy transfer. More evidence has been shown in Andrés et al (2022), which examines variations of third-order law with decomposition into parallel and perpendicular components using PSP data.…”
Section: Cascade Rate and Single Spacecraft Samplingmentioning
confidence: 91%